2020
DOI: 10.1371/journal.pone.0231707
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of high sodium intake with increased serum triglycerides on hypertension

Abstract: Background A high salt diet is associated with the development of hypertension, one of the most important cardiovascular risk factors. A reduction in sodium intake seems to have an effect on increasing serum triglycerides (TGs). Elevated TGs are independently linked to cardiovascular risk. However, there is limited evidence of a possible interactive effect of sodium intake and serum TGs on high blood pressure (BP). Methods We conducted a nationwide, population-based interaction analysis using the Kawasaki meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…e most abundant mineral element was K both in BFSR and GHSR, which agreed with the previous reports [5,33]. e Na/K ratios in BFSR and GHSR were 0.037 and 0.020, respectively, which was very low and indicated that it was an advantage from the nutritional point of view, because the intake of sodium chloride and diets with a high Na/K ratio have been related to the incidence of hypertension [34].…”
Section: Proximate Compositionsupporting
confidence: 89%
“…e most abundant mineral element was K both in BFSR and GHSR, which agreed with the previous reports [5,33]. e Na/K ratios in BFSR and GHSR were 0.037 and 0.020, respectively, which was very low and indicated that it was an advantage from the nutritional point of view, because the intake of sodium chloride and diets with a high Na/K ratio have been related to the incidence of hypertension [34].…”
Section: Proximate Compositionsupporting
confidence: 89%
“…In addition, the mechanism by which HSD increases triglycerides is still controversial but it is well known that high salt intake impairs lipid metabolism [9]. Interestingly, administration of Sp to HSD-fed animals did not normalize dyslipidaemia.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, HSD caused a signi cant decrease in plasma concentration of high-density lipoprotein and a signi cant increase in plasma concentrations of triglycerides, low density lipoprotein and total cholesterol, thus, showing an overt dyslipidaemia. Dyslipidaemia has been reported in different studies in association with metabolic syndrome, cardiometabolic dysfunction and salt-induced hypertension [9,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The good effects of fruits (Zhao et al, 2017) and vegetables (Blekkenhorst et al, 2018) are widely reported for their ultimate anti-atherogenic effects (Yusuf et al, 2004). Salty food increases the chance of developing hypertension (Rust & Ekmekcioglu, 2017;Choi et al, 2020), and fatty food causes hyperlipidemia (Kreisberg et al, 2005;Carson et al, 2020;Chiu et al, 2017). Sweetened foods increase the risk of cardiovascular events (Janzi et al, 2020), diabetes (Tseng et al, 2021), acne (Penso et al, 2020), and obesity Faruque et al, 2019).…”
Section: Discussionmentioning
confidence: 99%